The Mark Twain anthology : great writers on his life and works - Fishkin, Shelley Fisher (New York : Literary Classics of the United States : Distributed to the trade by Putnam Group, 2010)
Brings together the words of over 60 writers, from Twain's earliest reviews to today, probing the many facets of his incomparable humor, his revolutionary use of vernacular language, his exploration of the realities of American life, and his fearless opposition to the injustices and outrages of an imperialistic age.
Includes bibliographical references (p. 481-489) and index.
Keywords: Humorous stories, American